CLAPO syndrome. - Lamberg, O.; Strome, A.; Pedersen, E.; Eshaq, M. (European Journal of Pediatric Dermatology, 2022)
CLAPO syndrome (capillary malformation of the lower lip, lymphatic malformation of the face and neck, asymmetry of face and limbs, and partial/generalized overgrowth) is a rare congenital capillary malformation part of the PIK3CA related overgrowth spectrum (PROS). Given the associated partial or generalized overgrowth in CLAPO, it is critical to recognize this syndrome in patients and continue with close monitoring. Here we report a case of a 2-year-old girl who presented with CLAPO syndrome without associated hemihypertrophy.